REDES DE EMPRESAS E SEUS EFEITOS SOBRE O TURISMO - José Paulo Alves Fusco; Américo Tristão Bernardes; Angela Cabral Flecha; Alcides Volpato Castro e Silva (RAE: Revista de Administração de Empresas, 2012)
The relationships between firms, to be successful, demand high levels of transparency, information and physical flows of goods and services, in order to provide free access for all people involved in doing business together. The same can be said regarding flow of money resources and talents needed by the processes and operations performed by the network. Thus, the main idea involves reaching balance conditions in terms of sharing the results obtained by all participants, considering their objectives and goals, to keep the network form of organisation as being an adequate strategy. This proposal was defined from the authors’ expertise in analysis of tourism networks, together with results obtained on research in Ouro Preto. Thus it was possible to realize the weight of the players involved depending on the selection criteria used by visitors to configure their way into of the tourist region analyzed and thereby strengthen existing relationships.